2015
DOI: 10.1186/s12955-015-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-related quality of life using the SF-36 in Chinese cervical spondylotic myelopathy patients after surgery and its consistency with neurological function assessment: a cohort study

Abstract: BackgroundWe aimed to calculate the responsiveness and statistically prove the reliability of the Medical Outcomes Study Short Form Health Survey (SF-36) in a prospective cohort study. We investigated the profile of mid-term health-related quality of life (QOL) outcome assessments after surgery for cervical spondylotic myelopathy (CSM) and determined the consistency of the SF-36 assessments of neurological function.MethodsA total of 142 consecutive patients with CSM who underwent surgery were enrolled in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Similar to previous studies in both general[28, 29] and surgical populations [13, 30], which found a MCID of approximately five points, we calculated the MCID for PCS to be approximately four and MCS approximately six. While MCIDs are traditionally reported separately for PCS and MCS, the global assessment asks patients to rate their overall quality of life, not the physical or mental components.…”
Section: Discussionmentioning
confidence: 60%
“…Similar to previous studies in both general[28, 29] and surgical populations [13, 30], which found a MCID of approximately five points, we calculated the MCID for PCS to be approximately four and MCS approximately six. While MCIDs are traditionally reported separately for PCS and MCS, the global assessment asks patients to rate their overall quality of life, not the physical or mental components.…”
Section: Discussionmentioning
confidence: 60%
“…We also found that the independent predictor of recovery rate after ADF was identi ed as PCS score. A cohort study that investigated the surgical results of cervical spondylotic myelopathy showed that the recovery rate improvements correlated with SF-36's physical component domains [22], although both anterior and posterior surgery scores were included for the analysis. Collectively, when performing ADF, it may be important to have a thorough understanding of the patient's physical functioning prior to surgery to accurately predict the postoperative neurological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang [16] has recommended 0.70 as the minimal Cronbach's α coe cient of internal consistency that would indicate relatively good internal consistency reliability. The Cronbach's α coe cient of the speci c module was 0.81, and the split-half reliability was 0.65 in this study, indicating relatively good reliability of the speci c module.…”
Section: Discussionmentioning
confidence: 99%